Hybrid Energy Storage with PV for Islanded DC Microgrid - Poudel, Yam Krishna; Niraula, Dayasagar (Technical Journal, 2023)
Cogitating the present national as well as global context, renewable energy sources are becoming increasingly popular as a source of electricity in places, where connecting to the utility grid is either impossible or excessively costly. Several trends that have emerged as electrical distribution technology in the twenty-first century will change the requirements for energy transmission. Green power generating methods are receiving more attention due to the world's deteriorating environmental conditions, rowing prices, the limited nature of fossil fuels, and rising energy demand. The increasing depletion of fossil fuels and the escalating need for energy has made renewable energy sources a global topic of discussion. The incredible advancement of renewable energy has allowed us to address environmental problems. However, the production from these sources could be more predictable which requires an appropriate energy storage system. The main aim of this research paper is to study the hybrid energy storage with solar photovoltaic for islanded DC microgrid. This research study simulates, analyzes, and presents an islanded mode DC microgrid with solar PV, battery, and supercapacitor through the use of MATLAB Simulink. The MPPT (Maximum Power Point Tracking) system uses a twin-stage DC converter. The regulated Battery Energy Storage System (BESS), coupled through a bidirectional converter, helps to maintain a steady dc bus voltage. The transient and steady-state characteristics of the storage systems are examined. This study demonstrates how quickly hybrid energy storage can adapt to sudden changes in the load.